A feminist companion to the Hebrew Bible in the New Testament - Brenner-Idan, Athalya (Feminist companion to the Bible, 1996)
This volume is part of a series which provides a fundamental resource for feminist biblical scholarship, containing a comprehensive selection of essays, both reprinted and specially written for the series, by leading feminist scholars. The contributors to this volume are Lyn Bechtel, Mark Bredin, Athalya Brenner, Edna Brocke, Carole Fontaine, Lillian Klein, Amy-Jill Levine, Judith Lieu, Heather McKay, Adele Reinhartz, Jane Schaberg, Marla Selvidge, Leonore Siegele-Wenschkewitz, Beverly Stratton, Arie Troost, Pieter van der Horst, and Bea Wyler.